MANAJEMEN BENCANA (TAHAP PRA BENCANA, SAAT BENCANA, DAN PASCA BENCANA) DALAM PENANGGULANGAN BANJIR DI KOTA TANGERANG SELATAN - Sukma Adelia Putri, Azzani; Kismartini, Kismartini; Suwitri, Sri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Flooding remains an unresolved classic issue in South Tangerang City. To mitigate the resulting losses, disaster management is implemented in three phases: pre-disaster, during-disaster, and post-disaster. This study aims to analyze flood disaster management during these three phases. The research method used is descriptive qualitative, employing disaster management theory. Data collection techniques included interviews, observations, and documentation. The data obtained were analyzed using source triangulation techniques. The results indicate that pre-disaster management has been carried out through preparedness, early warning, and mitigation. Preparedness includes training, planning, and providing disaster equipment, though community participation is low due to busyness and elderly demographics. Early warning involves collaboration between BPBD and other agencies, but its reach is limited by funding and reliance on networks, with the BPBD website often experiencing downtime. Mitigation efforts include education and improving rainwater containment facilities, hindered by community awareness. During-disaster management involves evacuation and aid distribution. Evacuations are optimally performed, supported by SOPs, human resources, and equipment, though emergency aid distribution is uneven. Post-disaster management includes rehabilitation and reconstruction through collaboration with other agencies based on recommendations prepared by the Jitupasna Team. Execution is not optimal due to limited human resources, funding, and flood-prone terrain.